Etudes de modèles linéaires généralisés - Elkettani, Youssfi (Université Paris-Sud XI, Centre D'Orsay, 1984)
This is concerared with the generalised linear models : linear, loglinear, logit, probit models, etc...; and with the quasi-likehood models. The formulation, the fitting end the checking of theses models are developped. Quasi-likehood models are used for the study of the vitro cytotoxicity of chickens infected with Marek’s disease. The statistical software Genstat was used for the computations and tend out to be particulary adapted to exploiting these methods.
Keywords: Statistique; Modèle linéaire généralisé